2020
DOI: 10.3389/fonc.2020.01570
|View full text |Cite
|
Sign up to set email alerts
|

EI24 Inhibits Cell Proliferation and Drug Resistance of Esophageal Squamous Cell Carcinoma

Abstract: Drug resistance, whether intrinsic or acquired, often leads to treatment failure in esophageal squamous cell carcinoma (ESCC). Clarifying the mechanism of drug resistance in ESCC has great significance for reversing drug resistance, as well as improving the prognosis of patients. Previously, we demonstrated that etoposideinduced 2.4-kb mRNA (EI24) is the target of miR-483-3p, which promoted the growth, migration, and drug resistance in ESCC, suggesting that EI24 participates in repressing the tumorigenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…5B), and it was identified that EI24 expression in the overexpression group was notably lower compared with that in the NC group, suggesting that upregulation of miR-483 may inhibit the expression of EI24 protein. These results are consistent with our previous studies (24,28), suggesting a targeting relationship between miR-483 and EI24.…”
Section: Ei24 Expression Is Associated With Patient Prognosissupporting
confidence: 94%
See 2 more Smart Citations
“…5B), and it was identified that EI24 expression in the overexpression group was notably lower compared with that in the NC group, suggesting that upregulation of miR-483 may inhibit the expression of EI24 protein. These results are consistent with our previous studies (24,28), suggesting a targeting relationship between miR-483 and EI24.…”
Section: Ei24 Expression Is Associated With Patient Prognosissupporting
confidence: 94%
“…miR-483 expression is negatively associated with EI24 levels in CRC tissues. Our previous studies reported that the expression level of miR-483 was increased in esophageal squamous cell carcinoma, and that upregulation of miR-483 could promote the development of esophageal cancer (24,28). Furthermore, a reporter gene test confirmed that EI24 was the target molecule of miR-483 (21).…”
Section: Ei24 Expression Is Associated With Patient Prognosismentioning
confidence: 78%
See 1 more Smart Citation
“…EI24 is an important autophagy-associated protein and tumor suppressor that has been found to be under expressed in a variety of malignancies [ 90 , 91 , 92 , 93 ], although other studies have found no correlation or even positive correlation between EI24 expression and tumorigenesis in certain cancers, indicating that effects of EI24 depend on the cellular context of the cancers [ 94 , 95 ]. Additionally, EI24 regulates the UPS by targeting certain RING E3 ligases for autophagy mediated degradation; earlier studies have identified 161 RING E3 ligases as potential targets of EI24, the best characterized of which are TNFR-associated factor 2/5 (TRAF2/5), mouse double minute 2 homolog (MDM2), and tripartite motif containing 41 (TRIM41)—also called RING finger protein that interacts with C kinase 1 (RINCK1) [ 94 , 96 ].…”
Section: Molecular Components In the Intersections Of Ups And Autopha...mentioning
confidence: 99%
“…EI24 has been identified as a direct target of miR-483-3p (31). EI24, a p53-response protein, contains six transmembrane domains and suppresses cell growth through caspase 9 and mitochondrial pathways including in ESCC (32,33). Furthermore, EI24 has been shown to contribute to EMT (34).…”
Section: Mir-483-3p [Targeting Etoposide-induced 24 Transcript (Ei24)]mentioning
confidence: 99%